Now I am known : how a street kid turned foster dad found acceptance and true worth - Mutabazi, Peter (Baker Books, a division of Baker Publishing Group, 2022)
"From his childhood on the streets in Uganda to his life as an adoptive and foster father and work as an international advocate for children, Peter Mutabazi's story will inspire and empower you to find hope in the midst of hardship and live out the call that God places on each of us"--